Corporate philanthropy and performance: a case of a production company - Korsakienė, Renata; Marcinkevičius, Stasys (Business: Theory and Practice, 2013)
In recent years, companies have been encouraged to become socially responsible and invest into socially responsible activi-ties. The concept of social responsibility adopted in scientific literature is too complex and comprises corporate citizenship, sustainable development, management of stakeholders, environmental management, business ethics and corporate social performance. On the other hand, contemporary scientific literature about social responsibility emphasises the link between social responsibility and performance of a company. This paper focuses on analysis of social responsibility. The emphasis is placed on philanthropic responsibility and the link between the philanthropic responsibility and performance. Furthermore, it discusses tendencies of corporate social responsibility in Lithuania. The controversial views toward social responsibility have created preconditions to formulate the following research ques-tions: (1) Does a strong positive relationship between philanthropic responsibility and performance of a production company exist? (2) Is the relationship negative or inexistent? The obtained results of research have led to the conclusion, that philanthropic activity doesn’t increase profitability of a selected production company. The research of the authors contributes to other findings and implies that socially responsible activities of a company have a different impact on profit. Filantropinė įmonės atsakomybė ir veiklos rezultatai: gamybos įmonės atvejis SantraukaPastaruoju  metu  įmonės  skatinamos  tapti  socialiai  atsakingos  ir  investuoti  į  socialiai  atsakingą  veiklą.  Socialinės  atsakomybės samprata mokslinėje literatūroje yra itin kompleksiška, apimanti įmonės pilietiškumą, darnų vystymąsi, interesų grupių valdymą, aplinkos valdymą, verslo etiką ir įmonės socialinės veiklos rezultatus. Kita vertus, šiuolaikinė mokslinė literatūra verslo socialinės atsakomybės klausimais iš esmės pabrėžia socialiai atsakingos veiklos ir įmonės pelningumo sąryšį. Straipsnyje analizuojama socialinė atsakomybė. Dėmesys sutelkiamas į filantropinę atsakomybę ir jos ryšį su veiklos rezultatais. Aptariamos įmonių socialinės atsakomybės tendencijos Lietuvoje. Kontroversiškos nuomonės socialinės atsakomybės atžvilgiu sudarė pri-elaidas suformuluoti tokius tyrimo klausimus: ar egzistuoja teigiamas ryšys tarp gamybos įmonės filantropinės atsakomybės ir veiklos rezultatų, ar ryšys yra neigiamas, ar ryšys neegzistuoja. Gauti tyrimo rezultatai pasirinktos gamybos įmonės atveju sudaro prielaidas teigti, kad išlaidos filantropinei atsakomybei neturi įtakos pelnui. Straipsnio autorių atliktas tyrimas prisideda prie kitų rezultatų ir parodo, kad socialiai atsakinga įmonės elgsena turi nevienodą poveikį pelnui. Reikšminiai žodžiai: socialinė atsakomybė, filantropinė atsakomybė, veiklos rezultatai, gamybos įmonė, Lietuva.